Carlos García Gual, Diccionario de Mitos, Barcelona, Editorial Planeta (Diccionarios de Autor), 1997, 382 pp. y 8 de ilustraciones (Minerva, 2019)
Review: Carlos García Gual, Diccionario de Mitos, Barcelona, Editorial Planeta (Diccionarios de Autor), 1997, 382 pp. y 8 de ilustraciones